2017
DOI: 10.3390/ijms18040779
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Drivers of Pancreatic Cancer Pathogenesis: Looking Inward to Move Forward

Abstract: Pancreatic cancer (PC) continues to rank among the most lethal cancers. The consistent increase in incidence and mortality has made it the seventh leading cause of cancer-associated deaths globally and the third in the United States. The biggest challenge in combating PC is our insufficient understanding of the molecular mechanism(s) underlying its complex biology. Studies during the last several years have helped identify several putative factors and events, both genetic and epigenetic, as well as some deregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 218 publications
(260 reference statements)
0
45
0
2
Order By: Relevance
“…In MiaPaCa cells (Figure 2A), LEV showed a decrease on average size under moderate hypoxia (616.9 ± 217.9 nm), which increased somewhat under extreme hypoxia (751.6 ± 129.9 nm), compared to that under normoxic condition (732. 6 (Figure 2A and 2B).…”
Section: Evs From Pancreatic Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In MiaPaCa cells (Figure 2A), LEV showed a decrease on average size under moderate hypoxia (616.9 ± 217.9 nm), which increased somewhat under extreme hypoxia (751.6 ± 129.9 nm), compared to that under normoxic condition (732. 6 (Figure 2A and 2B).…”
Section: Evs From Pancreatic Cancer Cellsmentioning
confidence: 99%
“…However, under both moderate and extreme hypoxia, their levels kept on increasing in the CM ( Figure 1C, left panel). 6 normoxia. In AsPC1 cells, LEV and MEV release remained largely similar under normoxia and hypoxia except for significant difference recorded in MEV release at 24 hours.…”
Section: Hypoxia Increases the Release Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic factors play important roles in the development of pancreatic cancer. Multiple genetic studies have been implemented and identified some susceptibility genes for PC, such as KRAS, BRCA1, BRCA2, PALB2, FANCC, FANCG, ATM, CDKN2A, PRSS1, SPINK1, TERT, NR5A2, ZNRF3, and SMC2 . However, the genetic risk of PC explained by the reported candidate loci was limited, indicating the existence of undiscovered susceptibility loci for PCs.…”
Section: Introductionmentioning
confidence: 99%
“…for PC, such as KRAS, BRCA1, BRCA2, PALB2, FANCC, FANCG, ATM, CDKN2A, PRSS1, SPINK1, TERT, NR5A2, ZNRF3, and SMC2. 3 However, the genetic risk of PC explained by the reported candidate loci was limited, indicating the existence of undiscovered susceptibility loci for PCs.…”
mentioning
confidence: 99%